ANALISIS KOMODITAS UNGGULAN SEKTOR PERTANIAN DI KABUPATEN HULU SUNGAI SELATAN TAHUN 2012-2016 - MUHAMMAD RASYID; IKA CHANDRIYANTI (PPJP Universitas Lambung Mangkurat, 2019)
Muhammad Rasyid (2019). Analysis of Leading Agricultural Commodities In Hulu Sungai Selatan District 2012-2016. Advisor: Dra. Hj. Ika Chandriyanti, MP. This research was conducted to (1) analyze the superior commodities of the agricultural sector in South Hulu Sungai Regency and (2) analyze changes and structural shifts in agricultural sector commodities. This study uses the Location Quotient (LQ) analysis tool to find out what agricultural commodities are superior commodities in South Hulu Sungai Regency and use Shift Share analysis tools to find out changes and structural shifts in agricultural commodities inSouth Hulu Sungai Regency. The results of this study indicate that the leading agricultural commodities in the South Hulu Sungai Regency are the food crops sub-sector: lowland rice, upland rice and sweet potato. Plantation sub-sectors: coconut, cocoa, clove, candlenut, kapok, sugar palm, cinnamon, rubber and coffee. Fisheries sub sector: cage cultivation and floating net culture. Forestry sub-sector: sawn wood. Animal Husbandry Sub Sector: free range chickens, pigs and ducks. based on shift share calculation shows that the agricultural commodity which experienced the highest change or shift was found in the plantation sub-sector, namely the oil palm commodity.Keywords: Determination of the Main Commodities in the Agriculture Sector in South Hulu Sungai Regency.